THE EFFECTS OF AUDIT LAG, OPINION SHOPPING, LEVERAGE, AND PROFITABILITY TO THE GOING CONCERN AUDIT OPINION - Rizqah Hanie Pratiwi (JURNAL AKUNTANSI DAN AUDITING, 2019)
This study aims to determine the effect of audit lag, opinion shopping, leverage and profitability to the going concern audit opinion. The independent variables used in this study are audit lag, opinion shopping, leverage and profitability. The dependent variable used in this study is the going concern audit opinion. Data were obtained from audited financial statements and annual reports of manufacturing companies listed on the Indonesia Stock Exchange. The samples used were 26 companies during the period 2016-2018 with the total final sample being 78 samples. The sampling method is the purposive sampling method. The type of data used entirely is in the form of quantitative secondary data. This study uses a logistic regression analysis method. The result of this study indicate that leverage has a significant positive effect on going concern audit opinion, audit lag does not have a significant and negative effect on going concern audit opinion, opinion shopping does not have a significant and positive effect on going concern audit opinion, and profitability does not have a significant and negative effect on going concern audit opinion.